A Click‐Generated Triethoxysilane Tethered Ferrocene‐Chalcone‐Triazole Triad for Selective and Colorimetric Detection of Cu2+ Ions. Issue 13 (5th May 2017) - Singh, Gurjaspreet; Arora, Aanchal; Rani, Sunita; Kalra, Pooja; Kumar, Manoj
Abstract: This article describes an efficient synthetic approach to design ferrocene tailed chalcone appended triazole encapped organosilanes (7‐12 ) from acetylinic ferrocene precursors (1‐6 ). The synthesized compounds were well characterized by general spectroscopic techniques. The framed ligands were then evaluated for their ion sensing properties and were found to display significant perturbation in their absorption and emission behaviour upon addition of Cu 2+ ions. Their sensing ability is highly reversible on addition of ethylenediaminetetraacetic acid (EDTA) and hence can be employed as potential Cu(II) sensing materials. In addition, the presence of ferrocene functionality overtures an electro active unit generating a multiple signalling sensor that also offers naked eye detection of Cu(II) ions with analytical detection limit of as low as 10 μM. Above all, the designed chemosensor exhibits tolerance against other metal ions which enables the Cu 2+ ion detection even in a complex matrix. Complexation behaviour of one of the silanes, FCTS12 was also deliberated by computational analysis following DFT approach. Abstract : "Colorimetric Cu sensing via Ferrocene‐chalcone‐triazole triad"Ferrocene tailed chalcone appended triazole encapped organosilanes were designed following "click silylation" methodology. The framed ligands display significant perturbation in their optical behaviour upon addition of Cu 2+ ions even in a complex matrix. The chemosensor is highly reversible and ferrocene functionality overtures an electro active unit generating a multiple signalling sensor that also offers naked eye detection of Cu(II) ions.